Modified Screen-Printed and Carbon Paste as Ion-Selective Electrodes for the Determination of Ramipril Drug in Pharmaceutical and Biological Samples. Issue 3 (4th May 2019) - Mohamed, Gehad G.; Frag, Eman Yossri; Mohamed, Marwa El; Elhassan, Mohamed O.
Abstract: Ramipril was a prodrug and it was an angiotensin converting enzyme (ACE) inhibitor which can be used to treat congestive heart failure and hypertension. In this study, the electro activity and the performance characteristics of modified screen-printed (MSPEs) and carbon paste (MCPEs) electrodes with different types of ion pairs had been studied in order to determine ramipril (RAM) drug in pure solution, pharmaceutical formulations and biological fluid samples. The ion pair formation between RAM and phosphomolybdic acid (PMA) or phosphotungstic acid (PTA) or sodium teteraphenyl borate (Na-TPB) was the basis of preparation of modified ion selective electrodes used in this study. The surface analysis of the electrodes was studied using scanning electron microscope (SEM) and X-ray diffraction (XRD). The electrodes showed linear response with good Nernstian slope of 58.50±1.08, 59.00±0.96, 59.60±0.73 mV decade -1 for MSPEs modified with RAM-TPB, RAM-PMA and RAM-PTA ion pairs, respectively, and 59.20±0.96, 58.90±1.01 mV decade -1 for MCPEs modified with RAM-TPB and RAM-PTA ion pairs, respectively, over the concentration range from 5.0 x 10 -7 to 1.0 x 10 -2 mol L -1 . Although, the two types of electrodes provided response time of about 4 s for MSPEs and 5 s for MCPEs and exhibited lifetimes of 99 to 92 days for MSPE electrodes and 67 days for both electrodes of MCPEs on pH range from 2 to 5 for MSPEs and 2 to 4 for MCPEs. They showed high thermal stability according to the isothermal coefficients values. Selectivity coefficients of RAM sensors relative to a number of potential interfering materials were investigated. The developed method was found to be simple, precise and accurate when compared with the reported method.